The study on Ultra-fine WC-6 wt.%Co for producing cutting tool inserts - Mohd Shirul Hassan (Universiti Malaysia Perlis, 2009)
WC–Co cutting tools insert can be manufactured by controlling liquid phase migration or liquid redistribution during liquid phase sintering. In this study, the effect of temperature on mechanical properties has been studied. Sintering was done in controlled atmosphere (95% Nitrogen and 5% Hydrogen). Scanning Electron Microscope was used to characterize the microstructure. Sintered density was determined using Archimedes principle method while Rockwell Hardness scale A (HRA) was used to measure sintered samples hardness. Changes in dimension were measured with electronic digital caliper to study the shrinkage of samples. Microstructure was uniform for every sintering temperature. The result shows that at temperature 14500C, cutting tool has the optimum properties. At temperature 14500C the hardness and density were 89.18 HRA and 14.82 g/cm3 respectively. The highest rupture strength (TRS) also obtained at temperature 14500C with the value of 1573MPa.